Effect of Varieties and Biofertilizers on Growth and Yield of Mung Bean in Kailali, Nepal - Sharma, Raksha; Rajbanshi, Devraj; Bohara, Binod; Magar, Sangita Gaha; Sharma, Ganesh (Journal of Agriculture and Resource Management, 2024)
Mung bean, one of the most important crop in terms of food and nutritional security, is often neglected in terms of soil nutrient management in cereal based cropping system, where biological properties of soil is ignored and application of chemical fertilizers is at large. Hence this study was conducted at Agronomy Farm, Far Western University, Kailali, Nepal during April-June 2022 to evaluate varieties under different biofertilizers and their combination on yield and yield attributing traits of mung bean. The experiment was laid out in factorial randomized complete block design (RCBD) with three replications. The treatment consisted of 3 varieties of mung bean viz. Pratigya, Kalyan and SML-668 and 6 levels of biofertilizers viz. Rhizobium (R), Rhizobium+ Trichoderma (RT), Rhizobium+Pseudomonas (RP), Rhizobium+Trichoderma+Pseudomonas (RTP), Trichoderma+Pseudomonas (TP) and control. Growth and yield of mung bean were significantly influenced by variety, biofertilizers and their combinations but no significant interaction effects were observed. SML-668 performed better over Pratigya and Kalyan respectively in root parameters, leaf area index, yield attributing traits and yield generating 1.81 t/ha grain yield. Similarly, the combination of biofertilizers (RTP) generated significantly highest grain yield followed by RP and RT. The grain yield obtained with application of Rhizobium (R) was statistically at par with that from TP. The control plot yielded significantly lesser grain yield which was 7.6% lesser than rhizobium (R). So, the use of SML-668 variety and application of rhizobium either alone or in combination is recommended for better yield of mung bean at similar condition under rice-wheat cropping system.